Putting psychology in its place - Richards, Graham, 1941- author.
1 online resource (xix, 344 pages)
Keywords: "This fourth edition of Putting Psychology in its Place builds on the previous three in introducing the history of Psychology and placing the discipline within its historical and social contexts. Written by esteemed psychologists Graham Richards and Paul Stenner, this crucial text aims both to answer and raise questions about the role of Psychology in modern society by critically examining issues such as how Psychology developed and why psychoanalysis had such an impact. It discusses enduring underlying conceptual problems and examines how the discipline has changed to deal with contemporary social issues such as religion, race, and gender. The fourth edition features revised and updated chapters, though the core structure remains unchanged. The final chapter has been restructured and jointly re-written. This text was written to remain compatible with the British Psychological Society requirements for undergraduate courses, and is imaginatively written and accessible to all. Putting Psychology in its Place is an invaluable introductory text for undergraduate students of the history of Psychology and will also appeal to postgraduates, academics and anyone interested in Psychology or the history of science"--